Forward breeding for efficient selection. In Sustainability Sciences in Asia and Africa - Bohar, R.; Dreisigacker, S.; Lindqvist-Kreuze, H.; Kante, M.; Pandey, M.K.; Sharma, V.; Chaudhari, S.; Varshney, Rajeev K. (Springer, 2024)
Global food security is the numero uno priority in the current global situation, threatened by a number of challenges catalyzed by accelerated climate change and population growth. Crop improvement coupled with the modern plant breeding approaches, such as genomic-assisted breeding, is a proven solution to meet the food security. One of the key mandates in the modern plant breeding program is to combine the power of genomic selection into the breeding pipeline employing a low-cost genotyping solution. Several SNP marker-based platforms are now available depending on the objectives and field of application; despite the availability of different platforms, the public sectors face challenges in terms of funding and accessibility to the latest technology when compared to private sectors. Shared genotyping platform coupled with open breeding informatics involving different stakeholders with active support from donors will address several constraints faced by the public breeding program. Here, we summarize the available forward breeding genomic resources in the space of low-mid-density genotyping platform with special emphasis on shared services for four crop groups: 1. Wheat (cereal) 2. Potato (roots, tubers, and bananas (RTB crops)) 3. Groundnut (grain legumes) 4. Vigna species (legumes)